Osteocyte RANKL is required for cortical bone loss with age and is induced by senescence - Ha-Neui Kim; Jinhu Xiong; Ryan S. MacLeod; Srividhya Iyer; Yuko Fujiwara; Keisha M. Cawley; Li Han; Yonghan He; Jeff D. Thostenson; Elisabeth Ferreira; Robert L. Jilka; Daohong Zhou; et al. (JCI Insight, 2020)
In aging mice, osteoclast number increases in cortical bone but declines in trabecular bone, suggesting that different mechanisms underlie age-associated bone loss in these 2 compartments. Osteocytes produce the osteoclastogenic cytokine RANKL, encoded by Tnfsf11. Tnfsf11 mRNA increases in cortical bone of aged mice, suggesting a mechanism underlying the bone loss. To address this possibility, we aged mice lacking RANKL in osteocytes. Whereas control mice lost cortical bone between 8 and 24 months of age, mice lacking RANKL in osteocytes gained cortical bone during this period. Mice of both genotypes lost trabecular bone with age. Osteoclasts increased with age in cortical bone of control mice but not in RANKL conditional knockout mice. Induction of cellular senescence increased RANKL production in murine and human cell culture models, suggesting an explanation for elevated RANKL levels with age. Overexpression of the senescence-associated transcription factor Gata4 stimulated Tnfsf11 expression in cultured murine osteoblastic cells. Finally, elimination of senescent cells from aged mice using senolytic compounds reduced Tnfsf11 mRNA in cortical bone. Our results demonstrate the requirement of osteocyte-derived RANKL for age-associated cortical bone loss and suggest that increased Tnfsf11 expression with age results from accumulation of senescent cells in cortical bone.